Addressed challenges - Jung, Reiner; Paech, Barbara (Managed software evolution, 2019)
In this chapter, we discuss the diverse set of challenges, from different perspectives, that we face because of our aim to incorporate knowledge in software and processes tailored for software and systems evolution. Firstly, the discovery and externalization of knowledge about requirements, the recording and representation of design decisions, and the learning from past experiences in evolution form the human perspective, including developers, operators, and users. Secondly, performance and security induce the software quality perspective. Thirdly, round-trip engineering, testing, and co-evolution define the technical perspective. And fourthly, formal methods for evolutionary changes provide the foundation and define the formal perspective.
Gesehen am 11.12.2019